A new species of Altipolia (Lepidoptera: Noctuidae, Xyleninae) from China - Benedek, Balázs; Saldaitis, Aidas; Rimsaite, Jolanta (Zootaxa, 2014)
The trifine Noctuid genus Altipolia Plante occurs only in ecozones above the Himalayan timberline. The imagoes generally appear during late season’s first frosty nights with only females becoming active in early spring after overwintering. They share this reproductive strategy and certain genitalic characters with Dasypolia Thunberg and Estagrotis Nye. Members of Altipolia are medium sized moths (wingspan 31–38 mm) having divergent wings patterns and ground colouration but more conservative genitalia especially in most females. The genus is currently comprised of seven species which can now be separated into two species-groups based on male genitalia characters. Their distribution is restricted solely to the Himalayas where they are found from Northeast Pakistan throughout North India and Nepal to China’s North Yunnan and Western Sichuan Provinces. A more detailed survey of the late autumnal high mountain Himalayan Noctuidae fauna especially in the less explored areas of the Southern and Western edge of the Tibetan plateau may yield further species. Recent collecting trips to Western Sichuan resulted in new distribution data for a few interesting Altipolia species including one new to the science but also raised further taxonomical questions. The female genitalia of Altipolia are relatively uniform but further male genitalia analysis is needed and will be included in a subsequent study. The present paper provides an updated check-list of the genus including a description of a new species with a detailed comparison with its closest relatives.